EMPLEABILIDAD DE EGRESADOS DE LA FACULTAD DE CIENCIAS ADMINISTRATIVAS DE LA UNMSM - Tito Huamaní, Pedro Leonardo (2008)
The results of this research reveal that exist a medium correspondence among the environment of labor occupation defined by the university through its studies plans, and the level of employability and occupation of our graduates in the labor market. Such affirmation is corroborated when 53% of the polled declared that the know-how given in the University served a little or moderately for their optimum labor performance. It implies that the Faculty of Administrative Sciences of our University (UNMSM) should maintain a narrow communication with the stakeholders, in order to know which are their requirements in terms of professional resources to incorporate them in their future studies plans. Likewise, the investigation also shows that a representative percentage of our graduates have jobs in lower positions inside the structure organizacional, complying operating and administrative functions little or menacing nothing for the organization. This situation can be explained since two positions: a) That the polled were mostly graduates of recent years (2004-2006), that recently initiated professionally to labor, and is obvious that will do it from below, and b) That the plans of studies do not keep relation with what requires the labor market, for which our graduates systematically are deferred to elevate to functions or prominent positions, given that they are not found properly prepared for it. Contrasting and crossing other data, we can affirm that prominent little jobs of our graduates are explained for the first position, and at the same time shows an uncontrollable element in the investigation. In that order of ideas, the worry by level of employability and occupation of our graduates should be one of the main objectives of the Faculty; it implies that in the moment of restructure the plans of studies in the phase of diagnosis, they should be taken all the opinions and suggestions that emit the leaders and executives of the private or public organizations. We should understand that the employability is an a lot more dynamic concept than the employment, job or professional training. Working for the employability of our graduates implies to promote its competences to obtain works and to conserve them; this is a lot more than the process that conducts only to obtaining the Professional Title. In that context, the UNMSM should provide a balance between the technical formation and scientist for specialized works, without neglecting the formation of the citizen that is integrated to the company to transcend in the time. We advance in short to employability with integral formation of the man, that conjugates fundamentally the conceptual thing with the procedural thing and it attitudinal.